1998
DOI: 10.1128/aac.42.5.1207
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Test Conditions on Antifungal Time-Kill Curve Results: Proposal for Standardized Methods

Abstract: This study was designed to examine the effects of antifungal carryover, agitation, and starting inoculum on the results of time-kill tests conducted with various Candida species. Two isolates each of Candida albicans, Candida tropicalis, and Candida glabrata were utilized. Test antifungal agents included fluconazole, amphotericin B, and LY303366. Time-kill tests were conducted in RPMI 1640 medium buffered with morpholinepropanesulfonic acid (MOPS) to a pH of 7.0 and incubated at 35°C. Prior to testing, the exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
120
0
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(143 citation statements)
references
References 8 publications
5
120
0
5
Order By: Relevance
“…Klepser et al [34] demonstrated the ability of this methodology as an indispensable tool for assessing the activity of antimicrobials against bacteria. In fact this approach allows the estimation of drug antimicrobial activity as a function of time, which could be a more accurate determinant for clinical outcome of therapy than a simple numerical MIC or MMC [35].…”
Section: Effect Of CD Complexation On Triclosan Antimicrobial Activitmentioning
confidence: 98%
“…Klepser et al [34] demonstrated the ability of this methodology as an indispensable tool for assessing the activity of antimicrobials against bacteria. In fact this approach allows the estimation of drug antimicrobial activity as a function of time, which could be a more accurate determinant for clinical outcome of therapy than a simple numerical MIC or MMC [35].…”
Section: Effect Of CD Complexation On Triclosan Antimicrobial Activitmentioning
confidence: 98%
“…Significant antifungal carry-over [defined as a reduction in colony-forming units (CFU) >25% of the control] was excluded using standard methods [6]. The starting inoculum was 0.5-2.5 × 10 3 cells/mL.…”
Section: Antifungal Susceptibility Testingmentioning
confidence: 99%
“…Additionally, log-phase fungal cells (2 × 10 3 CFU/ml) were incubated with 10 μg of DMHF or 5 μg of amphotericin B used as a positive control. The culture was obtained and spread on YPD agar plate, and then the CFUs were counted after incubation for 24 h at 28°C (Klepser et al, 1998). The values were the average of triplicate measurements in three independent assays.…”
Section: Kinetics Of Microbial Killingmentioning
confidence: 99%